Answer:
-2755
Step-by-step explanation:
Answer:
Step-by-step explanation:
Simplify the expression -4x^2(3x − 7).
A. -12x^3 + 28
<h2>B. -12x^3 + 28x^2<= your answer</h2>
C. -12x^3 − 28
D. -12x^3 − 28x^2
Answer:
Answer: 4(x+1) over (x-5)
Step-by-step explanation:
A(b-c)=ab-ac
(1/7)(1/3h-1/2)=(1/7)(1/3h)-(1/7)(1/2)=1/21h-1/14
now we gots
6 and 1/7+1/21h-1/14
rearange
6 and 1/7-1/14+1/21h
make common denom which is 14
6 and 2/14-1/14+1/21h
6 and 1/14+1/21h
Answer:
~6.5 Levels
Step-by-step explanation:
2 levels every hour = 2:1
we take that ratio and multiply it by 3 for starters:
6 and half of our ratio
basically 6.5